Effect of an eco-friendly plasticizer on rheological, thermal and mechanical properties of biodegradable poly(propylene carbonate). (June 2016) - Hao, Yanping; Yang, Huili; Zhang, Huiliang; Zhang, Guibao; Bai, Yungang; Gao, Ge; Dong, Lisong
Abstract: A novel plasticizer poly(diethylene glycol adipate) (PDEGA) was synthesized via polyesterification reaction using diethylene glycol and adipic acid as raw materials. A series of poly(propylene carbonate) (PPC) blends were prepared by direct melt compounding with PDEGA as plasticizer. The miscibility, morphology, rheological properties, thermal behavior, and mechanical properties of the PPC/PDEGA blends were investigated. The blends were partially miscible systems with PDEGA uniformly dispersed in PPC matrix. Rheological study concluded that both unplasticized and plasticized PPC exhibited a slightly shear thinning behavior at all angular frequency regions. Viscosities of blends decreased as PDEGA content was increased due to increasing in chain mobility in the system. The plasticization decreased the glass transition temperature, which was reflected in a lower tensile strength and improved elongation at break. The pyrolytic decomposition activation energies of PPC and PPC/10 wt% PDEGA were estimated via Flynn-Wall-Ozawa method.